A Study of Knowledge and Practices Among Commercial Sex Workers Registered Under Jyoti Sangh STD Clinic, Ahmedabad - NJ Talsania; Rakesh Shah; Venu Shah; V Murugan (Medsci Publications, 2010)
Background: There is growing evidence about the importance of commercial sex workers (CSWs) and their clients as bridging groups for the HIV epidemic. In India, the role of CSWs is key to the future trajectory of the epidemic. Objective: To determine the level of knowledge and practices regarding STI/ HIV among CSWs. Study design: A Cross-sectional, community-based study. Methodology: The study was conducted in December 2005 among CSWs registered under Jyotisangh. Results: The mean age was 27.5 years and majorities (64.5%) of CSWs were below 35 years. Knowledge on some aspects of the diseases was quite low in the study group. A higher proportion of CSWs (73.5%) don't know the relationship between HIV and STI. About 66.3% of CSWs know one or more male STI symptoms. 58% of CSWs were aware of place for HIV testing. Majority (86.3%) of CSWs are attending counseling programme at Jyotisangh. 97.5% CSWs were aware about condom still 50.5% CSWs were regularly using condom with regular partner while nearly one fourth (26.5%) never used condom. And also 97% of CSWs never practiced anal intercourse with condom and only 25% reported either rarely/ sometimes non-penetrative sexual practice. Conclusion: High-risk behavior was established in the study sample. Safe sex and use of condom have to be energetically promoted among commercial sex workers.